Law and Mourning - Umphrey, Martha Merrill; Douglas, Lawrence; Sarat, Austin (Book collections on Project MUSE., 2017)
"[This book] brings together a distinguished group of scholars to explore the many and complex ways that law both regulates and gives meaning to our experience of loss. The essays in this volume illuminate how law helps us to absorb and contend with loss and its reverberations, channeling the powerful emotions associated with death and protecting those vulnerable to them. At the same time, law creates a regulatory framework for death as it establishes the necessity for a clear demarcation of the boundary between life and death, defines what we can and cannot do with the remains of the dead, and creates both privileges and disabilities for survivors. The contributors to the volume also explore how mourning generates critiques of existing legal and political orders which seem compelled by calls from the dead, unleashing an indifference to legal consequences in survivors that can undermine or destroy law." -- Publisher's website.